Barriers to Exclusive Breastfeeding among Urban Mothers (Journal of Enam Medical College, 2016)
Background: Breastfeeding is the unique source of nutrition and it plays an important role in the growth, development and survival of the infants. The initiation of breastfeeding within one hour and continuation of only breast milk up to six months ensure maximum benefits. The prevalence of exclusive breastfeeding in Bangladesh is 56% which is low. We designed this study to find out the factors influencing the duration of breastfeeding in Bangladeshi population.Objective: To study the factors influencing noncompliance to exclusive breastfeeding.Materials and Methods: This cross sectional study was conducted in Dhaka Shishu Hospital during the period January to June 2011. It includes 125 infant (112 months)-mother pairs randomly selected from the inpatient and outpatient departments of Dhaka Shishu Hospital. Mother-infant pairs were divided into two groups based on continuation of only breastfeeding up to six months. Outcomes were compared between two groups.Results: In this study exclusive breastfeeding was found in 27.2% and nonexclusive breastfeeding was in 72.8% cases. It was found that in most cases (40%) termination of breastfeeding was at 3--4 months. The study revealed that insufficient milk production due to poor position and attachment, social factors such as influence of husband and other family members, joining to service etc act as barrier to exclusive breastfeeding. Mass media and advice from health professionals had a higher influence on lower rate of exclusive breastfeeding. Women who were multiparous, housewives were more likely to maintain optimal breastfeeding.Conclusion: The present study reveals some important factors contributing to low rate of exclusive breastfeeding in Bangladesh.J Enam Med Col 2016; 6(2): 88-92